ChemInform Abstract: O‐Transfer‐Facilitated Cyclizations of Propargylamides with TMSN3: Selective Synthesis of Tetrazoles and Dihydroimidazoles. Issue 7 (January 2016) - Hu, Yancheng; Yi, Ruxia; Yu, Xinzhang; Xin, Xiaoyi; Wang, Chunxiang; Wan, Boshun
Abstract: In addition to the selective preparation of functionalized tetrazoles and diiodomethylated dihydroimidazoles, diiodomethylated dihydrooxazoles are prepared.